Spatializing the roughness length of heterogeneous urban surfaces to improve the WRF simulation-Part 2: Impacts on the thermodynamic environment. (1st February 2023) - Shen, Chong; Liu, Yiming; Shen, Ao; Cui, Yinping; Chen, Xiaoyang; Fan, Qi; Chan, Pakwai; Tian, Chunyan; Xie, Zizhao; Wang, Chunlin; Lan, Jing; Li, Xiaohui; et al.
Abstract: Roughness length (Z0 ) is a fundamental parameter in atmospheric boundary layer theory that affects the transfer of momentum and heat. However, this parameter in urban areas in the WRF model is typically assigned a fixed value. In a previous study, we developed a Z0 database for the heterogeneous urban underlying surface of Guangzhou and demonstrated that its application in the WRF model had significantly improved the simulations of wind speed. In this study, the impact of Z0 update on the dynamic and thermal environment in Guangzhou urban areas is investigated through two numerical experiments: the base experiment applies the model-default Z0 value (0.5 m) for the urban areas and the sensitivity one uses a heterogeneous Z0 map (with higher Z0 values in most urban areas) estimated in the previous study. The results show that the temperature and relative humidity at 2 m height are not sensitive to this Z0 modification. For the dynamic environment, the modification of Z0 decreases the wind speed at 10 m height and increases the friction velocity. The reduction of horizontal wind speed due to Z0 increases reaches heights of several hundred meters, especially below a height of 400 m (950 hPa). Additionally, the updated Z0 leads to an increase in the turbulent momentum exchange coefficient over the urban underlying surface, resulting in a more vigorous turbulent mixing and elevated planetary boundary layer height. For the thermal environment, the Z0 increases result in a higher turbulent heat exchange coefficient near the surface layer, which contributes to the vertical heat flux transport. Moreover, the Z0 increase enhances the sensible heat flux during daytime and reduces the land surface temperature and ground heat flux in Guangzhou central urban area. Due to the reduced heat storage during the daytime, the amount of heat released at night decreases accordingly, thus causing a reduction in the land surface temperature at night and a decrease in the sensible heat flux. This study provides a comprehensive understanding of the sensitivity of the thermodynamic environment to the urban Z0 increase and reconfirms the significance of a realistic Z0 dataset in atmospheric modeling. Graphical abstract: Image 1 Highlights: The effect of Z0 modifications on spatiotemporal variations of meteorological factors was explored. Horizontal wind speed reduction due to Z0 increases reached heights of several hundred meters. Surface energy balance was used to illustrate the impact of Z0 increases during daytime and nighttime.